(untitled) (Research, Society and Development, 2021)
The objective of this study was to assess the alterations in the glycoproteins of the jejuno and the ceco of commercial poetry by histochemical techniques, and they will be subjected to different programs of forced molting. The study occurred in aviary of FCAV-Unesp, Jaboticabal campus. Thirty-two 58-week old Hisex Brown laying hens were used, housed in laying cages (two birds/cage) and randomly distributed in four forced molting programs with two production cycles, ending in 28 and 140 days, respectively. Four birds were allocated to each group, distributed into: Group 1 (G1), in which the California method was used as a control; group 2 (G2), in which a low-calcium diet was used; group 3 (G3), in which a diet with a high level of zinc was provided, and for group 4 (G4), a diet with a low level of sodium. The fragments of jejunum and cecum were submitted to the histochemistry techniques: PAS, PAS + amilase, AB 0,5 and AB 2,5 and were observed the glycoprotein, glycogen, sulfated and carboxyled polysacharides, respectively. The results suggest that the different treatments of forced molting in the experimental conditions did not interfere in the integrity of intestinal cells of these segments. It is concluded that the four treatments of forced molting did not interfere with the presence of intestinal cellular polysaccharides as well as with the integrity of the morphology of the intestinal cells and the glycocalyx.